Zapalenie tylnej części twardówki u dziecka – opis przypadku - Chipczyńska, Barbara; Grałek, Mirosława; Klimczak-Ślączka, Dorota; Kanigowska, Krystyna; Sarti, Grażyna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
We present the case of 13-years old girl with recurrent unilateral painful proptosis and associated with other ocular features: loss of vision, disc edema, macular edema, folds at the posterior pole. Ultrasound examination with CT scan were necessary to make the differential diagnosis of orbital tumors. The patognomonic sign „T” on B scan was extremely essential in the clinical diagnosis of posterior scleritis.